Tools and Mechanisms for Attracting Investment in the Sustainable Innovative Sphere - ORYNBASSAROVA, Yerkenazym; KUDAIBERGENOVA, Saltanat; DARIBEKOVA, Aigul; AKANAYEVA, Tolkyn; TISHTYKBAYEVA, Arnagul (Journal of Environmental Management and Tourism, 2018)
The article deals with the mechanisms of attracting investment in the innovative and sustainable sphere of the Republic of Kazakhstan, as well as the tools of state support for innovations. The programs of granting innovative grants in nine directions are reflected in this article, as well as technology parks implementing these programs. The role of leading research institutes and universities in the field of innovation. The systems of preferential taxation of priority directions in the sphere of innovations based on SEZ.